αシヌクレインの伝播機序とレビー小体病の創薬戦略 - 川畑, 伊知郎; 福永, 浩司 (日本薬理学会年会要旨集, 2022)
Intracellular accumulation of α-synuclein is a pathological hallmark of Lewy body diseases, including Parkinson's disease and Dementia with Lewy bodies. Accumulation of pathogenic proteins is associated with the process of uptake into neuronal cells. Various molecules participate in the α-synuclein uptake and propagation. Here, we introduce the unique process of α-synuclein uptake and show the impact of fatty acid-binding protein 3 (FABP3) with dopamine D2 receptors. FABP3 is rich in dopaminergic neurons and interacts with dopamine D2 receptors, specifically the long type (D2L), abundant in caveolae. We demonstrated that mesencephalic neurons with tyrosine hydroxylase (TH)+, FABP3-/-, D2L-/- do not take up α-synuclein. Likewise, dynasore, a dynamin inhibitor, and caveolin-1 knockdown also abolished the uptake. Second, we advance the possible preventives for α-synuclein propagation. We found that the deletion of α-synuclein C-terminal end abolished the uptake to dopaminergic neurons. Additionally, exposure to the C-terminal peptides alleviated the α-synuclein uptake. The antagonistic action on the α-synuclein-FABP3 binding is different from the FABP3 ligands. Based on these data, we propose a novel pathogenic mechanism of Lewy body diseases and potential therapeutic medicines targeting the α-synuclein uptake process.